Kondisi fisik kerabang telur ayam ras petelur cokelat di Pasar Pinasungkulan Manado - Wakur, Nison; Tangkere, E.S.; Lambey, L.J.; Kowel, Y.H.S. (Universitas Sam Ratulangi, 2021)
THE EGGSHELLS’ PHYSICAL CONDITION OF BROWN CHICKEN EGGS AT PINASUNGKULAN MARKET MANADO. A study was conducted to examine the eggshells’ physical condition of fresh-brown chicken eggs (table eggs) at the Pinasungkulan market, in Manado city. The variables taken were egg weight in three general size categories (small, medium and large) and eggshells condition (cleanliness, smoothness/ texture and color). The averages egg weight of the fresh-brown chicken eggs in three size categories made by egg sellers were 51.57 grams for small size eggs, 62.03 grams for medium size eggs and 70.68 grams for large size eggs, respectively. The eggshells’ condition values of fresh-brown eggs were from slightly clean to clean (3.58 - 3.82) on cleanliness; from slightly smooth to smooth (3.64 - 3.85) on texture; and from slightly faded to brown (2.79 - 3.85) on color. T-test paired was showed that the eggshells’ physical condition of small size eggs was better than that of medium size and large size eggs seen from their eggshells’ cleanliness, smoothness/ texture and their color, It found also that the egg seller in Pinasungkulan Market, Manado had not been carefully made and well standardized the egg size or egg weight categories.Keywords: brown eggs, eggshell, cleanliness, smoothness/texture, color.